Criminal Legal Policies Toward The Release of Conpriants During The Covid 19 Pandemic in The Ius Constituendum - Dian Priono, Yamin; Rifai Rahawarin, Ahmad (Pusat Publikasi Nusantara, 2023)
Criminal law policy on the release of convicts during the Covid 19 pandemic in the ius constititum , namely carrying out criminal law policies through spending for convicts and children through assimilation . As well as release for convicts and children through integration in the form of parole, parole and leave before being free) . This policy is carried out by applying certain conditions so that it does not maximally reduce the number of inmates in correctional institutions to reduce the risk of spreading Covid-19. Whereas the criminal law policy regarding the release of convicts during the Covid 19 pandemic in the ius constituendum, namely in the Corrections Bill, there is the concept of restorative justice as a means of social integration, but the formulation of this concept has not been clearly implemented, so it is necessary to use the concept of restorative justice at the post-adjudication stage as a means to reduce correctional inmates as well as recovery of victims and their original condition. As well as in the RKUHP implicitly there is a concept of conversion of the sanction system but it has not been clearly formulated, so there is a need for the concept of conversion of the sanction system as an alternative in an effort to reduce correctional inmates to prevent prison overcapacity.